Peningkatan Sumber Daya Siswa Kelas XII SMK Negeri 1 Tanjung Morawa Melalui Penerapan Soft Skill - Rismaja Putra; Surya Sevi Wijayanna; Zainal; Fauzan Azim (Sevaka : Hasil Kegiatan Layanan Masyarakat, 2025)
With the existence of SMK Negeri 1 Tanjung Morawa, it is expected to contribute to educating the nation's children in the Tanjung Morawa District, Deli Serdang Regency. This research employs a Mixed Methods Research approach, which combines quantitative and qualitative methods, analyzing the graduates of SMK Negeri 1 Tanjung Morawa Vocational School and the needs of the global industry. Soft skills education is essentially a reflection of an individual's personality characteristics. It is important for students to apply soft skills such as motivation, respect for others, teamwork, self-discipline, self-confidence, work ethic, adherence to common norms, communication skills (both verbal and written), leadership, creativity, ambition, responsibility, and adaptability.